Efficacy and Safety of Tumour Necrosis Factor-α Antagonists for Folliculitis Decalvans: A Retrospective Case-series Pilot Study - Aurore Dupont; Alexia Eyraud; Brigitte Milpied; Sylvie de Bataille; Eline Cassassa; Anne-Sophie Darrigade; Thomas Barnetche; Marie-Sylvie Doutre; Bruno Matard; Marie Beylot-Barry; Julien Seneschal (Medical Journals Sweden, 2023)
Folliculitis decalvans is a chronic inflammatory skin disease leading to scarring alopecia. Management of this disabling disease is difficult and no treatment is currently approved. Current knowledge regarding the pathogenesis of folliculitis decalvans suggests the benefit of using anti-tumour necrosis factor-α. This pilot study aimed to evaluate the clinical efficacy of anti-tumour necrosis factor-α for management of folliculitis decalvans. A single-centre retrospective pilot study included patients with refractory folliculitis decalvans treated by tumour necrosis factor-α inhibitors. An Investigator's Global Assessment (IGA) score was designed and validated to assess the efficacy of the therapy. Response to treatment was considered good to excellent when an IGA ≤ 2 was obtained at month 12. Eleven patients were included, with a mean time from diagnosis of folliculitis decalvans to the introduction of infliximab (n = 9) or adalimumab (n = 2) of 8.55 ± 1.26 years. Nine patients had failed on at least 2 lines of systemic therapies before starting anti-tumour necrosis factor-α. The median IGA score at baseline was 3. At the end of follow-up, 5 patients were considered responders. Overall, the safety profile of anti-tumour necrosis factor-α was good. The results suggest that the clinical benefit of anti-tumour necrosis factor-α is obtained after at least 6 months of treatment. However, further prospective studies are needed to confirm these results.